Sustainable Lake/Situ Management: CASE STUDY : SITU IN BOGOR CITY - Andi Setyo Pambudi (Indonesian Journal of Applied Research (IJAR), 2021)
The increasingly advanced developmentnin the city of Bogor has an impact on the carrying capacity of the environment. One that is rarely in the spotlight is about the decreasing number of lakes in Bogor. In urb an areas such as Bogor City, local people refer to the lakes as situ or setu. The existence of these “Situ” affects the water system, both in this city and in the surrounding areas. Although “Situ” play a vital role in maintaining the balance of urban water systems, they have not received sufficient attention in the planning documents for the City of Bogor, both annual and medium-term documents. The rapid development of the city affects thequantity and quality of urban lake water in the city of Bogor. These “Situ continue to experience physical and ecological degradation which increases the threat to the health of the population of the city of Bogor. This situation shows that the site has not been managed and functioningnproperly. Human and natural disturbances such as encroachment, garbage disposal, and untreated waste have polluted “Situ” water and reduced its volume capacity. Most of the lakes in the city of Bogor experience disturbances in damaged environmental conditions. This paper seeks to examine th e condition of the “Situ” in Bogor City and its problems based on literature studies from previous researchers. The results of the research will provide recommendations based on scientific theories and existing regulations, both national regional regulations and regional regulations in Bogor City